Compactive Viscosity of Snow and Its Climatic Implications at Mizuho Station, Antarctica (Special Issue of the Proceedings of the First Symposium on Antarctic Meteorology and Glaciology) - Norikazu MAENO; Hideki MAEDA (National Institute of Polar Research, 1979)
The compactive viscosity coefficient of snow was obtained from a density profile at Mizuho Station, Antarctica The value of the compactive viscosity coefficient was by two orders of magnitude larger than that of ordinary seasonal snow. The large value was attributed to strong bonds between constituent ice particles within Antarctic snow which had been aged for prolonged periods A sharp peak of the compactive viscosity coefficient was found in a limited range of the depth around 35 m, that is in a range of the density around 750 kg m^ In the depth range from 30 m to 40 m the layer-to-layer densities varied largely and the mean density deviated markedly from a smoothed general trend. These results suggest that a colder climate occurred repeatedly and lasted approximately 300 years before the present in the vicinity of Mizuho Station